Social support and psychological distress across different age groups in Argentine adults - María Agustina Aceiro; Gisela Delfino; Francisco González Insua; Lina Grasso; Solange Rodríguez Espínola (Revista de Psicología)
Psychological distress (PD) involves a deficit in emotional capacities. Social support (SS), structural and functional, is a protective factor for health as it reduces stress and distress. Previous literature indicates that both variables are related and vary throughout adulthood. Based on a cross-sectional study (n=5388; 53.7% women; age: 18-98, M=43.15; SD=17.38), we aimed to analyze whether age is a moderating factor in the relationship between SS and PD in adulthood. A deficit in SS is related to PD, and age moderates between them. The relationship between PD and structural SS is more potent in older adults, while instrumental and informational SS is more robust in younger adults. Affective SS is the best predictor of PD regardless of age.